THE WAYS OF OVERCOMING SYSTEMIC CRISIS OF MILITARY INDUSTRY (THE CASE OF SEVERODVINSK CITY) - A. V. Novikov (Real Economics Publishing House, 2014)
The article is devoted to main problems of Russian military industry enterprises, where as an example the shipbuilding companies of Severodvinsk city are represented. The crisis development is historically observed as well as the current situation. The main attention is paid to clusters forming mechanisms, where clusters are to be formed on the smart basis of restructuring and merging of companies and their parts, processes. The restructuring levels and kinds are presented.